Pengaruh Transparansi Keberlanjutan, Persepsi Greenwashing dan Literasi ESG Terhadap Kepercayaan Investor Muda - Jumriaty Jusman; Ika Fausiah; Nurfadilah Nurfadilah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The background of this research is based on the growing attention of the younger generation toward sustainability issues and responsible investment practices, making it important for companies and regulators to understand the factors that shape investor trust. This study aims to analyze the influence of Sustainability Transparency, Perceived Greenwashing, and Environmental, Social, and Governance (ESG) Literacy on Young Investors’ Trust. This study employs a quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS). The research sample consists of young investors from the Islamic Economics and Business Faculty at UIN Palopo who meet the specified criteria. The model testing includes evaluating both the outer model and inner model through analyses of validity, reliability, path coefficients, and R². The results of the study show that ESG Literacy has a positive and significant effect on Young Investors’ Trust, while Sustainability Transparency and Perceived Greenwashing do not have a significant influence. These findings indicate that young investors’ understanding of ESG principles plays a more decisive role in shaping trust compared to mere sustainability reporting disclosure or perceptions of greenwashing. Practically, this study provides implications for issuers, capital market authorities, and financial education providers to enhance the quality of ESG literacy and to ensure that sustainability information is delivered in a more educational and accessible manner.